KINERJA PEGAWAI DISADMINDUKCAPIL SURAKARTA: ANALISIS LINGKUNGAN KERJA DAN MOTIVASI - Sukma Bayu; Esti Dwi Rahmawati; Khabib Alia Akhmad (Kampus Akademik Publiser, 2024)
This study aims to analyze the performance of employees at the Department of Population and Civil Registration in the City of Surakarta, influenced by the work environment and motivation. The population in this study consists of all employees of the Department of Population and Civil Registration in the City of Surakarta, with the sample criteria being temporary employees (TKPK) who have worked for more than 6 months, resulting in a total sample of 49 employees. The data used in this study includes both primary and secondary data, collected through observation, interviews, and questionnaires. The analysis technique employed is Structural Equation Modeling-Partial Least Square (SEM-PLS) and the data processing technique uses the SmartPLS4 program. The results of this study indicate that the work environment has a positive but not significant effect on employee performance, while motivation has a positive and significant effect on employee performance.